Outras cartografias: a narração de espaços e sujeitos à margem em romances de Conceição Evaristo e Maria Valéria Rezende - Silveira, Raquel Mariane da (2020)
This dissertation presents a study about the novels Becos da memória (2006), by Conceição Evaristo, and Quarenta dias (2014), by Maria Valéria Rezende, in which the spoiled identities of the ongoing urbanization process in Brazil are represented. Such identities and the spaces they are relegated to are presented, in both works, from the perspective of their narrators, whose social perspectives and places of speech – in the terms of Young (2006) and Ribeiro (2019), respectively – are notably distinct and offer unique spatial representations. The main objective of this work becomes, therefore, to analyze how the narrative spatiality is constructed in the two novels, through an approach that prioritizes the interconnection between the represented spaces and the narrative voices that present them, whose subjectivities are configured as filters under which the fictional architecture is outlined. It seeks to examine, through this analysis, the different narrative strategies mobilized by Evaristo and Rezende in the representation of spaces on the margins in two metropolises: Belo Horizonte’s slum in Becos da memória, and the slum and suburbs of Porto Alegre in Quarenta dias. For this purpose, in addition to the narrative focus, the configuration of the represented spaces is considered, in terms of their positioning, the circumscribed temporality (ies) and their (anti) aesthetics. Understanding the nature of these spaces and, mainly, the way they are represented, makes it possible to outline the subjectivities of the narrators, as also the communities that are there, which make up the horizon of literary cartography.